2019
DOI: 10.1039/c8dt04940h
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate and phosphite encaged in frameworks constructed from square lanthanum aminopolycarboxylates and sodium chloride

Abstract: Lanthanum aminopolycarboxylates, Na12n[La(edta)L]4n·8nNaCl·4nH2O (1: L = HPO32−; 2: L = CO32−) and K12n[La(cdta)(CO3)]4n·35nH2O (3), with square structures were obtained. Carbonate 2 possesses 3.7 Å diameter holes that can adsorb a small amount of O2 or CO2 selectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…For lanthanide carbonato complexes, the common coordination numbers of Ln(III) are 8, 42-44 9, 42,45 and 10. 38,46…”
Section: Crystal Structuresmentioning
confidence: 99%
“…For lanthanide carbonato complexes, the common coordination numbers of Ln(III) are 8, 42-44 9, 42,45 and 10. 38,46…”
Section: Crystal Structuresmentioning
confidence: 99%
“…While most investigations of the carbonatebridged polynuclear Ln III complexes have been focused on solid state characterization only, [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]53 reports concerning detailed solution studies of such compounds are limited. [47][48][49]54,[56][57][58][59][60][61] In fact, some research revealed that the dimeric and trimeric carbonate-bridged polynuclear Ln III complexes may dissociate in solution, resulting in the equilibrium mixture. 47,[56][57][58]…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49]54,[56][57][58][59][60][61] In fact, some research revealed that the dimeric and trimeric carbonate-bridged polynuclear Ln III complexes may dissociate in solution, resulting in the equilibrium mixture. 47,[56][57][58]…”
Section: Introductionmentioning
confidence: 99%